ATP and T-cell-mediated rejection. Issue 1 (February 2018) - Castillo-Leon, Eduardo; Dellepiane, Sergio; Fiorina, Paolo
Abstract : Purpose of review: Purine nucleosides and nucleotides are released in the extracellular space following cell injury and act as paracrine mediators through a number of dedicated membrane receptors. In particular, extracellular ATP (eATP) significantly influences T-lymphocyte activation and phenotype. The purpose of this review is to discuss the role of ATP signaling in the T-cell-mediated alloimmune response. Recent findings: In various animal models of solid transplantation, the purinergic axis has been targeted to prevent acute rejection and to promote long-term graft tolerance. The inhibition of ATP-gated P2X receptors has been shown to halt lymphocyte activation, to downregulate both Th1 and Th17 responses and to promote T-regulatory (Treg) cell differentiation. Similarly, the inhibition of ATP signaling attenuated graft-versus-host disease in mice undergoing hematopoietic cell transplantation. Significantly, different drugs targeting the purinergic system have been recently approved for human use and may be a viable therapeutic option for transplant patients. Summary: The inhibition of eATP signaling downregulates the alloimmune response, expands Treg cells and promotes graft survival. This robust preclinical evidence and the recent advances in pharmacological research may lead to intriguing clinical applications.